2007
DOI: 10.1073/pnas.0709597104
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B1 biosynthesis in plants requires the essential iron–sulfur cluster protein, THIC

Abstract: Vitamin B1 (thiamin) is an essential compound in all organisms acting as a cofactor in key metabolic reactions and has furthermore been implicated in responses to DNA damage and pathogen attack in plants. Despite the fact that it was discovered almost a century ago and deficiency is a widespread health problem, much remains to be deciphered about its biosynthesis. The vitamin is composed of a thiazole and pyrimidine heterocycle, which can be synthesized by prokaryotes, fungi, and plants. Plants are the major s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(168 citation statements)
references
References 41 publications
4
162
0
Order By: Relevance
“…Tobacco mutants in thiamine biosynthesis exhibited a 50% reduction in chlorophyll pigments that was also fully reversible by the addition of exogenous thiamine (McHale et al, 1988). A similar result was also obtained in the Arabidopsis ThiC insertion mutants that were blocked in the biosynthesis of the pyrimidine moiety of the thiamine molecule, producing albino plants that exhibited slow growth, even though starch and sucrose levels accumulated up to 40 and 50% more, respectively, than wild-type plants (Raschke et al, 2007;Kong et al, 2008).…”
Section: Tkox Plants Display Partial Thiamine Auxotrophysupporting
confidence: 64%
“…Tobacco mutants in thiamine biosynthesis exhibited a 50% reduction in chlorophyll pigments that was also fully reversible by the addition of exogenous thiamine (McHale et al, 1988). A similar result was also obtained in the Arabidopsis ThiC insertion mutants that were blocked in the biosynthesis of the pyrimidine moiety of the thiamine molecule, producing albino plants that exhibited slow growth, even though starch and sucrose levels accumulated up to 40 and 50% more, respectively, than wild-type plants (Raschke et al, 2007;Kong et al, 2008).…”
Section: Tkox Plants Display Partial Thiamine Auxotrophysupporting
confidence: 64%
“…AtTHIC was expressed strongly in leaves, flowers and siliques, but only with a trace expression in roots (Figure 9A). Raschke et al [34] recently reported that the Considering that AtTHIC is involved in thiamine biosynthesis, we analysed the effect of extrinsic thiamine supplementation on AtTHIC expression. One-week old seedlings were transferred to MS plates supplied with different thiamine concentrations (0, 0.5, 1.0, 10, 100 and 1 000 mg/L) and were grown for 1 day.…”
Section: Expression Profiles Of Atthicmentioning
confidence: 99%
“…The arrangement of the two functional domains in one protein results in the coordinated synthesis of the two enzymes for thiamine biosynthesis. More recently, Raschke et al [34] described that Arabidopsis THIC is an iron-sulfur cluster protein and is involved in thiamine biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis thaliana, three enzymes participate together in the synthesize of thiamin monophosphate (TMP), namely, TH1 (Ajjawi et al, 2007a), THI1 (Belanger et al, 1995;Machado et al, 1996), and the TPP riboswitch-regulated THIC (Bocobza et al, 2007;Raschke et al, 2007;Wachter et al, 2007;Kong et al, 2008). Unlike in prokaryotes where TMP can be directly converted into TPP (Begley et al, 1999), in Arabidopsis, TMP is subsequently dephosphorylated into thiamin (Komeda et al, 1988), which is then pyrophosphorylated into TPP by the thiamin pyrophosphokinases (TPKs), namely, TPK1 and TPK2 (Ajjawi et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%